Perbaikan Perencanaan Penjadwalan Maintenance Pada Air Conditioner (AC) Menggunakan Metode Realibility Centered Maintenance (RCM) Di PT. Tifico Fiber Indonesia Tbk - Fatma, Nur Fadilah; Ponda, Henri; Saputra, Trio Adi (Journal Industrial Manufacturing, 2022)
In this era of global competition, companies are required to increase productivity in their companies so that they can compete with other companies. One of the indicators in increasing productivity is the level of reliability of the production machines in the company. In measuring how good the reliability of a production machine is, an effective and efficient maintenance process is needed for the company. In this case the Air Conditioner or hereinafter abbreviated as AC is one of the indoor air conditioning devices. One company that uses an Air Conditioner or AC to support the production process and the activities of its employees, especially those working in the production room, is PT Tifico Fiber Indonesia Tbk. The purpose of this study is to determine the critical components and the appropriate interval of Air Conditioner maintenance. Then a study was conducted to propose maintenance scheduling time intervals using the Reliability Centered Maintenance (RCM) method and to determine critical components using the Failure Mode Effect and Analysis (FMEA). From the research, it was found that the critical components of the splite type Air Conditioner component were the outdoor fan motor with an RPN value of 120, a compressor with an RPN value of 200, an outdoor capacitor with an RPN value of 140 and an indoor pcb with an RPN value of 168. Mean Time To Repair (MTTR), Mean Time To Failure (MTTF) Reliability Centered Maintenance (RCM) method obtained by outdoor fan motors for 13 days, compressors for 10 days, outdoor capacitors for 90 days and indoor pcb for 24 days.Keywords : Maintenance, Reliability Centered Maintenance (RCM), Mean Time To Repair (MTTR), Mean Time To Failure (MTTF), Failure Mode Effect and Analysis (FMEA).